Characterization Of Fiber Weave Effect On High Speed Pcbs - Ong , Yee Lun (2015)

(untitled)
The growth of innovation and development megatrend shaped the modern computing era for half a century and still counting. Today, switching signals are required to have faster rise and fall time with relative high signal integrity to meet higher digital signaling bandwidth. Therefore, it is very important to ensure reliable signal transmission link between the transmitter and receiver as the signal propagated through system channels will experience signal distortion, degradation especially in long haul transmission path. In this work, a methodology for printed circuit board (PCB) modeling is proposed which includes fiber weave fabrics to investigate the impact of fiber weave effect on high speed differential signaling. In order to achieve close representation of actual commercial PCB, 3-Dimension (3D) simulation models were developed through Keysight Technologies EMPro simulation software. Meanwhile, Keysight Technologies ADS simulator was deployed to further perform channel characterization. The correlation study between ideal 2-Dimension (2D) and 3D electromagnetic (EM) models showed good agreement with theory. The simulated results showed high flatness index spread glass weave such as 1086-style outperformed sparser weave like 1080 and 2113-style with lower insertion loss, wider eye width and eye height, and lowest timing skew at 0.44 ps in test case 1. Besides that, it is found that trace to weave position full misalignment induced extra timing skew at 2.12 ps in test case 2. Lastly, wider trace width and trace to trace separation at 6 / 10.9 mils is proven to have better overall channel performance at targeted 100 Ω differential impedance fixed variable set in test case 3.